P1706 Trilogy of stroke. (17th January 2020) - Koenig, A; Moser, M; Dannenberg, V; Bergler-Klein, J; Binder, T; Gabriel, H; Schneider, M
Abstract: A 53 y/o female patient presented with clinical signs of stroke. Substantial cardiovascular risk factors were present with arterial hypertension, hyperlipidemia, impaired glucose tolerance, and a history of smoking. Transthoracic echocardiography revealed a suspicious structure on the aortic valve. Consequently, transesophageal echocardiography (TEE) was ordered. In TEE, the structure proved to be highly suspicious for fibroelastoma. In addition, significant plaque of the aortic arch, and a persistent foramen ovale (PFO) were diagnosed in this examination. The patient was referred to cardiac surgery for excision of the mass on the aortic valve and for PFO closure. This case stresses the importance of echo in patients presenting with stroke. Apart from left atrial thrombus, several other possible embolic substrates can be diagnosed.